2001
DOI: 10.17796/jcpd.25.4.fl062x558qtt4v69
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric dental procedures under general anesthesia at the Amiri hospital in Kuwait

Abstract: Ninety-six patients, fifty-eight healthy patients and thirty-eight special needs patients, ranging in age from 3 to 31yr (average age 6.9yr) had received dental treatments under general anesthesia (GA) at Amiri Hospital. The mean number of dental procedures per child was 13.6 (SD±5.4) with a mean number of 15.6 procedures for healthy patients and 10.5 special needs patients. There was a statistically significantly higher number of dental procedures for healthy patients than for special needs patients (p&lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 4 publications
9
22
1
Order By: Relevance
“…As a result, special needs children do not develop a need for treatment until they reach higher age. In a recent study, the mean age in a group of ASA (American Society of Anaesthesiologists Physical Status Classification) I and II and in a group of ASA III and IV patients were similar [30], whereas another study found an age difference similar to the one found in our study [18]. The later explanation, however, seems to be supported by data obtained in this study as special needs patients were older at referral and had a less comprehensive total treatment need than non‐special needs patients.…”
Section: Discussionsupporting
confidence: 76%
“…As a result, special needs children do not develop a need for treatment until they reach higher age. In a recent study, the mean age in a group of ASA (American Society of Anaesthesiologists Physical Status Classification) I and II and in a group of ASA III and IV patients were similar [30], whereas another study found an age difference similar to the one found in our study [18]. The later explanation, however, seems to be supported by data obtained in this study as special needs patients were older at referral and had a less comprehensive total treatment need than non‐special needs patients.…”
Section: Discussionsupporting
confidence: 76%
“…22 It has been reported that in hospital settings, the frequency of DGA is concentrated in patients affected with cardiac problems, asthma, physical and emotional disabilities. 28 However, in a study carried out in Spain it was reported that the main frequency of oral rehabilitations under DGA were in intellectual disability, cerebral palsy, epilepsy, and Down syndrome patients. 29 This frequency is quite similar to this outpatient DGA study, suggesting that demographic, ethnic and treatment facilities play a major role in each study.…”
Section: Discussionmentioning
confidence: 98%
“…This study agrees with the reports indicating that the number of dental procedures such as pulpotomies and stainless steel crowns are placed more often in healthy children than MCDD children. 28 Currently, outpatient anesthesia is increasing in all medical fields due to the reductions in costs related to the elimination of extended hospital stays. This reduction in medical expenses enables lower income families a better opportunity to obtain safe, comprehensive preventive and restorative care.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be associated with the high prevalence of caries and an increased number of teeth present in the mouth in the ASA II-III group (maximum of 32 teeth) versus the younger ASA I patients (<4 years old; maximum of 20 teeth). However, more pulpotomies were conducted on ASA I patients (46.9%) than on ASA II-III patients (23.5%), likely due to the fact that a pulpotomy is a treatment performed on primary teeth, that is, on young patients, as is the case of ASA I patients under 4 years old 19,20 . We did not find significant differences with respect to extractions.…”
Section: Discussionmentioning
confidence: 99%